A Murine Monoclonal Antibody With Potent Neutralization Ability Against Human Adenovirus 7 - Wang, Rong; Lu, Jiansheng; Zhou, Quan; Chen, Lei; Huang, Ying; Yu, Yunzhou; Yang, Zhixin (Frontiers in Cellular and Infection Microbiology, 2019)
B1-type human adenoviruses (HAdVs) HAdV-3, HAdV-7, and HAdV-55 have caused epidemics in North America, Asia, and Europe. However, to date, no adenovirus vaccines or antiviral drugs have been approved for general use. In the present work, a scFv-phage immune library was constructed and mouse monoclonal antibody (MMAb) 10G12 was obtained through selection. 10G12 is specific for HAdV-7 and binds the hexon loop1 and loop2 (LP12), resulting in strong neutralization activity against HAdV-7. Additionally, it is stable in serum and buffer at various pH values. The findings provide insight into adenovirus and antibody responses and may facilitate the design and development of adenovirus vaccines and antiviral drugs.